Pengaruh Rasio Bungkil Kedelai dan Kacang Gude Terhadap Karakteristik Tahu - B.A. Susila Santosa; Narta Narta; S. Widowati (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1998)
Soybean oil cake and pigeonpea were the alternatives vegetable protein sources besides soybean. Their high protein content has not been considered yet in the food processing technology especially for tofu product. This study evaluated ratio of soybean oil cake to pigeonpea used in tofu processing, tofu characteristics and recovery, anti nutrition content and organoleptics characteristics of tofu. Ratio of soybean oil cake to pigeonpea used in this study were 100:0; 90:10; 80:20; 70:30; 60:40; and 50:50. The result showed that ratio of soybean oil cake to pigeonpea effected tofu characteristics and recovery. Ratio 100:0 gave the best result either in nutrition (protein) content or recovery, but the tofu contains the highest anti nutrition too. Tofu made from material with ratio of 90:10 and 80:20 had the same characteristics and better than others. Organoleptically, tofu made from material with ratio 100:0; 90:10 and 80:20 were valued higher than others. This study needs to be developed in order to find the best processing technique and condition in larger scale.